Global identification of RsmA/N binding sites in Pseudomonas aeruginosa by in vivo UV CLIP-seq. Issue 12 (2nd December 2021) - Chihara, Kotaro; Barquist, Lars; Takasugi, Kenichi; Noda, Naohiro; Tsuneda, Satoshi
ABSTRACT: Pseudomonas aeruginosa harbours two redundant RNA-binding proteins RsmA/RsmN (RsmA/N), which play a critical role in balancing acute and chronic infections. However, in vivo binding sites on target transcripts and the overall impact on the physiology remains unclear. In this study, we applied in vivo UV crosslinking immunoprecipitation followed by RNA-sequencing (UV CLIP-seq) to detect RsmA/N-binding sites at single-nucleotide resolution and mapped more than 500 binding sites to approximately 400 genes directly bound by RsmA/N in P. aeruginosa . This also verified the ANGGA sequence in apical loops skewed towards 5ʹUTRs as a consensus motif for RsmA/N binding. Genetic analysis combined with CLIP-seq results suggested previously unrecognized RsmA/N targets involved in LPS modification. Moreover, the RsmA/N-titrating RNAs RsmY/RsmZ may be positively regulated by the RsmA/N-mediated translational repression of their upstream regulators, thus providing a possible mechanistic explanation for homoeostasis of the Rsm system. Thus, our study provides a detailed view of RsmA/N-RNA interactions and a resource for further investigation of the pleiotropic effects of RsmA/N on gene expression in P. aeruginosa .